Microscopic Extrathyroidal Extension Results in Increased Rate of Tumor Recurrence and Is an Independent Predictor of Patient’s Outcome in Middle Eastern Papillary Thyroid Carcinoma - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Qadri, Zeeshan; DeVera, Felisa; Siddiqui, Khawar; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Oncology, 2021)
Background: Papillary Thyroid Cancer (PTC) is the most common endocrine malignancy, with recurrence rate as high as 30%. A great deal of controversy surrounds the significance of microscopic extrathyroidal extension (m-ETE) as a prognostic factor. The most recent edition (8th) of American Joint Committee on Cancer (AJCC) staging system has removed m-ETE from the definition of pT3, which suggests that m-ETE may lack prognostic impact in PTC patients. Moreover, data about m-ETE prevalence and clinical impact on Middle Eastern PTC remains unknown. We therefore investigate the prevalence of m-ETE and its clinico-pathological correlation and prognostic impact in Middle Eastern PTC. We also compared the AJCC 7th and 8th staging systems and their prognostic performance. Methods: PTCs from 1430 consecutive adult patients from single tertiary care hospital were included in this study. A retrospective analysis of PTC patients’ survival and recurrence were compared between AJCC 8th and AJCC 7th staging systems using Proportion of Variation Explained (PVE) and Harrell’s C-index. Results: Median follow up of the study cohort was 9.3 years. 31.2% (446/1430) of patients had m-ETE. In the overall cohort, m-ETE was associated with multiple adverse features such as older age (p < 0.0001), male sex (p = 0.0245), tall cell variant (p < 0.0001), bilateral tumors (p < 0.0001), multifocality (p < 0.0001), lymphovascular invasion (p < 0.0001), lymph node metastasis (p < 0.0001), distant metastasis (p = 0.0166), tumor recurrence (p < 0.0001), radioactive iodine refractoriness (p < 0.0001), BRAF mutation (p < 0.0001) and reduced recurrence-free survival (RFS; HR = 2.54; 95% CI = 1.93 – 3.33; p < 0.0001) irrespective of tumor size. Of the 611 patients with T3 disease based on AJCC 7th edition, 359 (58.8%) were down-staged in AJCC 8th edition classification. Overall, the prognostic performance of AJCC 8th edition was inferior to AJCC 7th on the basis of lower PVE (3.04% vs. 3.73%) and lower C-index (0.40 vs. 0.48). Conclusions: In Middle Eastern PTC, m-ETE is significantly associated with compromised survival and acts as an independent predictor of RFS. Given these findings, m-ETE should be included in the thyroid cancer treatment guidelines.